De Facto China Yuan Exchange Rate Regime and Fluctuation Estimation - Chen, Zili (2014)
This dissertation first adopts the exchange rate regression model for investigating the evolution of de facto CNY exchange rate regime after the China announced the currency reform. To simultaneously assess the volatility range of residuals in the regression model, that shows the deviation degree of the CNY fluctuation with respect to the basket currencies. Finally the dynamic VaRs of the CNY exchange rate is calculated based on the current exchange rate regime. The entire research process constitutes an inferential framework for estimating actual exchange rate regime and its risk. The main results are shown as follows. (1) In the nine years after the currency reform, the exchange rate regime of CNY was approximately pegged to USD all the time, and the CNY had slightly increased flexibility and slow appreciation during the second segment [2006-04-23, 2008-12-17] and the fourth segment [2010-06-21, 2014-08-15]. (2) Under current exchange rate regime, the 95% VaR by GARCH (1,1)-t model is the best risk estimate to describe the upper risk bound of residual series, and the 5% VaR by GARCH (1,1)-ged model the best risk estimate to describe the lower risk bound of residual series.